The STAR event plane detector - Adams, John Raymond; Ewigleben, A.; Garrett, S.; He, W.; Huang, T.; Jacobs, P. M.; Ju, X.; Lisa, M. A.; Lomnitz, M.; Pak, R.; Reed, R.; Schmah, Alexander; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2020)
The Event Plane Detector (EPD) is an upgrade detector to the STAR experiment at RHIC, designed to measure the pattern of forward-going charged particles emitted in a high-energy collision between heavy nuclei. It consists of two highly-segmented disks of 1.2-cm-thick scintillator embedded with wavelength-shifting fiber, coupled to silicon photomultipliers and custom electronics. We describe the general design of the device, its construction, and performance on the bench and in the experiment.
Gesehen am 28.10.2020